(untitled) (Altre Modernità, 2015)
In this essay I will explore Naipaul’s novel The Enigma of Arrival (1987), focusing on the problematic theme of identity in relation to visual perception. It is my aim to analyze how his use of visual art – with particular reference to painters John Constable and Giorgio de Chirico – confirms the preeminence of visual fruition on other forms of experience in the development of the narrative. First, I will expose Naipaul’s choice to deliver to his readership a text that complicates not only the idea of national belonging, but also the notions of literary genre and canon. Then, I will focus on a close reading of the first section of the novel by analyzing his use of the term pairs see/know and change/death. Finally, I will show that it is along these two traces and, more specifically, along the preferential trajectory of sight, that the narrator interrogates himself about his quest for identity. The narrator approaches both Constable’s and De Chirico’s paintings through reproductions and he strongly emphasizes the second-hand quality of his experience of art fruition. Rather than a matter of purely aesthetic observations, Naipaul’s focus on reproductions is a means through which the narrator gives voice to his colonial anxieties in a changing world. The window can serve as a useful metaphor – and indeed, it frequently appears in the text – for the obstacles, fences, and filters that separate subject and object of observation.